Social practices in human rights in middle education institutions in the department of Boyacá: From the student perspective (Quaestiones Disputatae: temas en debate, 2017)
One of the worries in school and Colombian society is associated with the inquiryinto the teaching and practice of human rights that take place in scholastic institutions. In this sense, this question takes into account the student perspective in high school and university, we wanted to know which are the practices that affect human rights in middle education institutions in Boyacá?We started with the initial belief that administrators, as well as teachers and students’ parents are power agents that contravene students’ human rights, making them the most affected population at school and their context. We noticed the need to highlight practices of living with human rights that allow us to raise scenarios which improve education and faithful practices of human rights at school.
Keywords: education; discrimination; human rights; social practice